2017
DOI: 10.1183/16000617.0080-2016
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen therapy for interstitial lung disease: a systematic review

Abstract: This review aims to establish the impact of oxygen therapy on dyspnoea, health-related quality of life (HRQoL), exercise capacity and mortality in interstitial lung disease (ILD).We included studies that compared oxygen therapy to no oxygen therapy in adults with ILD. No limitations were placed on study design or intervention type. Two reviewers independently evaluated studies for inclusion, assessed risk of bias and extracted data. The primary outcome was dyspnoea.Eight studies evaluated the acute effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
89
0
13

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(103 citation statements)
references
References 26 publications
(103 reference statements)
1
89
0
13
Order By: Relevance
“…46 Oxygen therapy in ILD lacks robust data as highlighted in a recent meta-analysis reviewing the impact of oxygen on dyspnoea, quality of life, exercise capacity and mortality in ILD patients. 47 Whilst improvement in exercise capacity was observed, no demonstrated mortality benefit was seen in any of the referenced studies. Pulmonary rehabilitation has demonstrated benefit in ILD patients, albeit that the benefit is not sustained once exercise programmes cease.…”
Section: Treatment Of Ildmentioning
confidence: 98%
See 1 more Smart Citation
“…46 Oxygen therapy in ILD lacks robust data as highlighted in a recent meta-analysis reviewing the impact of oxygen on dyspnoea, quality of life, exercise capacity and mortality in ILD patients. 47 Whilst improvement in exercise capacity was observed, no demonstrated mortality benefit was seen in any of the referenced studies. Pulmonary rehabilitation has demonstrated benefit in ILD patients, albeit that the benefit is not sustained once exercise programmes cease.…”
Section: Treatment Of Ildmentioning
confidence: 98%
“…Van Manen et al propose an ABCDE approach with A ssessment of patients’ needs and values; B acking with education; C o‐morbidities and comfort care; D isease‐modifying treatment and E nd‐of‐life care (Figure ) . Oxygen therapy in ILD lacks robust data as highlighted in a recent meta‐analysis reviewing the impact of oxygen on dyspnoea, quality of life, exercise capacity and mortality in ILD patients . Whilst improvement in exercise capacity was observed, no demonstrated mortality benefit was seen in any of the referenced studies.…”
Section: Treatment Of Ildmentioning
confidence: 99%
“…Various exercise tests, including walk tests, treadmill tests and cycle ergometry, have been used for in-laboratory assessments. For both diseases, supplemental oxygen therapy has consistently been shown to improve exercise performance during in-laboratory tests, with some reporting a reduction in exertional dyspnoea [62,63]. In addition to small study populations, most of these in-laboratory assessment studies had inadequate study design with a lack of blinding and randomisation.…”
Section: Ambulatory Oxygen Therapy In Copd and Ildmentioning
confidence: 99%
“…Acute administration of oxygen therapy has been shown to improve exercise capacity during exercise tests in patients with ILD. 10,11 A recent short-term non-blinded crossover trial in patients with ILD indicated potential improvement of quality of life with the use of ambulatory oxygen therapy. 12 However, the long-term effects of ambulatory oxygen therapy in patients with ILD and exertional desaturation have not been evaluated.…”
Section: Introductionmentioning
confidence: 99%